Proline Promotes Drought Tolerance in Maize - Pirzada Khan; Ashraf M. M. Abdelbacki; Mohammed Albaqami; Rahmatullah Jan; Kyung-Min Kim (Biology)
Drought stress significantly affects maize (Zea mays L.) growth by disrupting vital physiological and biochemical processes. This study investigates the potential of proline supplementation to alleviate drought-induced stress in maize plants. The results show that proline supplementation enhanced shoot and root growth under normal conditions and alleviated drought-induced reductions in growth parameters. Under drought stress, proline increased shoot length by 40%, root length by 36%, shoot fresh weight by 97%, root fresh weight by 247%, shoot dry weight by 77%, and root dry weight by 154% compared to the untreated plants. While drought stress induced electrolyte leakage and reduced the relative water content (RWC) and leaf area, proline treatment mitigated these effects by improving membrane stability, water retention, and chlorophyll content. Moreover, proline supplementation reduced hydrogen peroxide (H2O2) and malondialdehyde (MDA) levels by 38% and 67%, respectively, in the drought-stressed plants compared to the untreated controls. It also enhanced catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD) activities by 14%, 69%, and 144%, respectively, under drought stress, indicating a strengthened antioxidative defense. Proline also increased the protein content and improved N, P, and K retention by 30%, 40%, and 28%, respectively, in the drought-stressed plants, supporting metabolic and osmotic balance. Additionally, proline improved endogenous proline and sugar levels, facilitating osmotic adjustment and providing energy reserves. These findings suggest that proline supplementation effectively enhances maize resilience under drought stress, improving growth, reducing oxidative stress, and enhancing osmoprotection.